Chemically-induced photoreceptor degeneration and protection in mouse iPSC-derived three-dimensional retinal organoids - Shin-ichiro Ito (Stem Cell Research, 2017)
Induced pluripotent stem cells (iPSCs), which can be differentiated into various tissues and cell types, have been used for clinical research and disease modeling. Self-organizing three-dimensional (3D) tissue engineering has been established within the past decade and enables researchers to obtain tissues and cells that almost mimic in vivo development. However, there are no reports of practical experimental procedures that reproduce photoreceptor degeneration. In this study, we induced photoreceptor cell death in mouse iPSC-derived 3D retinal organoids (3D-retinas) by 4-hydroxytamoxifen (4-OHT), which induces photoreceptor degeneration in mouse retinal explants, and then established a live-cell imaging system to measure degeneration-related properties. Furthermore, we quantified the protective effects of representative ophthalmic supplements for treating the photoreceptor degeneration. This drug evaluation system enables us to monitor drug effects in photoreceptor cells and could be useful for drug screening.